Unveiling the correlation between metacognitive skills, argumentation skills, and problem-solving ability in the realm of biology education - Siswati, Bea Hana; Prihatin, Jekti; Suratno, Suratno; Hariyadi, Slamet; Wahono, Bevo (Universitas Ahmad Dahlan, 2024)
Metacognition refers to the capacity for supervising, arranging, and directing the process of learning, while argumentation skills encompass the aptitude to construct and validate logical points. Proficiency in problem-solving holds a crucial role within the realm of scientific education. This research aims to explore the interconnection between metacognitive skills, argumentation skills, and problem-solving abilities in the domain of biology education. Employing a correlational research design, the investigation encompassed 118 students engaged in biology studies within the University of Jember's Biology Education Study Program during the academic term of 2022/2023, specifically within the Introduction to Education Science course. The research instrument utilized was a survey featuring 10 queries for each category—metacognitive skills, argumentation skills, and problem-solving abilities. Statistical analysis involved inferential methods, particularly multiple linear regression correlation. The findings unveiled a positive correlation between students' metacognitive skills and argumentation skills and their adeptness in problem-solving within the context of biology learning, signified by a noteworthy p-value of 0.000 (p < 0.05). This finding shows the importance of developing metacognitive skills and argumentation skills in improving students' problem solving abilities in learning. The implication of this finding can be used to design more effective learning strategies in improving metacognitive skills, argumentation skills and students' problem solving in biology subjects